MED23‐associated intellectual disability in a non‐consanguineous family. (2nd April 2015) - Trehan, Aditi; Brady, Jacqueline M.; Maduro, Valerie; Bone, William P.; Huang, Yan; Golas, Gretchen A.; Kane, Megan S.; Lee, Paul R.; Thurm, Audrey; Gropman, Andrea L.; Paul, Scott M.; Vezina, Gilbert; et al.
Abstract : Intellectual disability (ID) is a heterogeneous condition arising from a variety of environmental and genetic factors. Among these causes are defects in transcriptional regulators. Herein, we report on two brothers in a nonconsanguineous family with novel compound heterozygous, disease‐segregating mutations (NM_015979.3: [3656A > G];[4006C > T], NP_057063.2: [H1219R];[R1336X]) in MED23 . This gene encodes a subunit of the Mediator complex that modulates the expression of RNA polymerase II‐dependent genes. These brothers, who had profound ID, spasticity, congenital heart disease, brain abnormalities, and atypical electroencephalography, represent the first case of MED23‐ associated ID in a non‐consanguineous family. They also expand upon the clinical features previously reported for mutations in this gene. © 2015 Wiley Periodicals, Inc.